Surgical Imperatives in Benign Follicular Nodular Disease: Redefining Malignancy Risk and the Role of Total Thyroidectomy. - Dewana, Azhy Muhammed; Gurumallesh Prabu, Poorani (BioMed Research International, 2026)
Background: Goiter is the most prevalent endocrine illness, and it is considered endemic when > 10% of a community has it. The patient may not notice the nodules, which typically form early in endemic goiter and later in sporadic goiter. Objectives: The objective of this study is to determine the incidence, histopathological subtypes, and risk of thyroid malignancy in patients with goiter, and to evaluate the diagnostic performance of ACR TI‐RADS‐guided fine‐needle aspiration cytology (US‐FNAC) using the Bethesda System for Reporting Thyroid Cytopathology 2023. Patients and Methods: This prospective, cross‐sectional descriptive study recruited patients with goiter in the Rizgary Teaching Hospital, Erbil, Iraq, from January 2020 to December 2024. Clinical and sonographic examinations were performed to confirm the diagnosis. To reduce the possibility of malignancy in goiter, a preoperative UG‐FNAB was performed. Patients underwent surgery; biopsies were analyzed, and histopathological analysis of surgically removed thyroid tissue was performed to determine the goiter type, Bethesda category, and malignancy status. Results: Among 128 diagnosed patients with goiter, 76 (59.4%) were diagnosed with BFN, in which most of them were females (n = 63, 82.9%), with a median age of 36 years. UG‐FNAB indicated colloid goiter in 28 (36.74%) cases, follicular neoplasm/suggestive malignancy in three (3.94%) cases, malignant in seven (9.2%) cases, and inconclusive in 35 (46.1%) cases. Based on the Bethesda Classification (2023), FNAC results indicated that Bethesda Category I (nondiagnostic or unsatisfactory) was more commonly detected (n = 35, 46.1%), followed by Category II (benign) (n = 28, 36.8%), whereas Category III (atypia of undetermined significance) was not detected (n = 0, 0%). Categories IV (follicular neoplasm or suspicious follicular neoplasm) and V (suspicious for malignancy) were found in three cases each (3.94% each), and Category VI (malignant) in seven cases (9.2%). The histopathological analysis found 15 (19.7%) individuals had a TC, including papillary carcinomas (n = 8, 53.3%), follicular carcinomas (n = 4, 26.6%), Hurthle cell carcinomas (n = 2, 13.3%), and anaplastic carcinoma (n = 1, 6.6%). Additionally, patients with BFN were 3.35 times more likely to develop thyroid cancer than those with a solitary thyroid nodule. Conclusions: The incidence of goiter is slightly high among patients in this locality, especially median‐aged females. However, the incidence of TC is low when successfully treated with total thyroidectomy.